Effect of Broiler Prices on Logistics and Supply Chains In Developing The Poultry Industry In Egypt - Shehata, Gaber Ahmed Bassyouni; El-Kawy, Abd El-Kareem E. Abd; Zahran, Hanan A.; Kamal, Ehab M. (Advances in Social Sciences Research Journal, 2021)
This study aimed to study the effect of changes of broiler prices on the profitability of broiler logistics under Egyptian conditions. This study was undertaken during the period 2016 – 2020 on random cycles of both broiler and layer farms in three different provinces which were Menofia, Kaliobia and Giza. The data were collected from a cross-sectional survey on the broiler and during the data collection the researcher was contact with the poultry holders and managers. The data were collected from the accurate records which available in the poultry farms of the study areas and from the structured questionnaires methods which established by the researcher and admitted to the farmers during the time of interview, also, the data collected from the Agricultural Directorates of governorates, Livestock development sector and Economic Affairs Sector. The data includes data about logistics costs, returns and net prpfits of broiler production, the data were analyized statistically and economically. The price of broilers considered as the main variable affecting the profitability of broiler production farms. The price of poultry affected by the costs of production costs that includes variable and fixed costs The results, concluded that, the higher prices of broiler prices observed during the years 2018, 2019 and 2020 than that of years 2016 and 2017 and in winter seasons than the summer seasons. The increasing of broiler prices causes increasing returns level for broiler sales, the summer seasons achieved a higher net profit than the winter seasons due to increasing the level of production costs in winter seasons than the summer seasons.